The Applicability of the Strategic Killing Model to the Case of the Armenian Genocide in the Ottoman Empire (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
In the course of human history, most wars and revolutions have resulted in the enormous loss of civilian life, often due to the intentional elimination by power elites of ethnical and political diversity within the territorial confines of their nation-states and beyond. Genocide is the term coined by Raphael Lemkin in 1944 to define the deliberate elimination of a national, political, ethnical, or religious group, in whole or in part, whether by a state or a non-state power group. While genocides have taken place throughout the history of human civilization, only recently had the academia begun to investigate the causal factors of mass killing. Political theorists assess the significance of both micro and macro-scale factors conducive to violent behavior and genocide in societies. However, a more precise approach is critical to enhance the understanding of the mechanisms that generate acts of mass killing in various spatio-temporal settings and to develop adequate and timely policy measures to avert and cease mass killing in any part of the world. The atrocities committed by the Nazi regime against civilian populations in Germany and across Europe, the ethnic cleansing campaigns and mass murder of ethnical communities perpetrated by the Khmer Rouge regime and Pol Pot in what is now Cambodia and in the former Yugoslavia by the Milosevic regime; the Hutu-led killing of the Tutsi population in Rwanda and the recent events in Darfur have all stressed the leading role of ruling elites in the organization and implementation of genocide. Developing a proper approach that conforms to these dramatic historical experiences is not only an academic objective but also an ethical priority that will lay the foundation for effective policy mechanisms to prevent genocide and bring about justice and peace for future generations.